Leadership Principles for Today's Residential Real Estate Brokers - Derek Farnsworth; Jennifer Clark; Aarambh Shah; Allen F. Wysocki (EDIS)
This publication discusses leadership principles for residential real estate brokers in the US. It highlights the challenges brokers face, such as market volatility and declining demand, and offers strategies to overcome these issues. Original publication date May 2011.